2016
DOI: 10.1590/s1679-45082016rw3088
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal pressure: an integrative review

Abstract: There is a growing request for measuring intra-abdominal pressure in critically ill patients with acute abdominal pain to be clarified. Summarizing the research results on measurement of vesical intra-abdominal pressure and analyzing the level of evidence were the purposes of this integrative literature review, carried out based on the databases LILACS, MEDLINE and PubMed, from 2005 to July 2012. Twenty articles were identified, in that, 12 literature reviews, 4 descriptive and exploratory studies, 2 expert op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 16 publications
0
44
0
10
Order By: Relevance
“…Other literatures, reported that the incidence of vomiting ranged from 12% to 50 % (Momenfar et al, 2018). Nurses should be routinely monitor GRV to ensure gastric empty (Mohamed et al, 2013) Critically ill patient recognized to have IAP up to 7 mmHg, developed IAH at 12 mmHg and considered ACS at 20mmHg with organ dysfunction (Milanesi & Caregnato, 2016). In the present trail, the IAP readings of both groups are within accepted level and not exceed to be IAH.…”
Section: Discussionmentioning
confidence: 46%
“…Other literatures, reported that the incidence of vomiting ranged from 12% to 50 % (Momenfar et al, 2018). Nurses should be routinely monitor GRV to ensure gastric empty (Mohamed et al, 2013) Critically ill patient recognized to have IAP up to 7 mmHg, developed IAH at 12 mmHg and considered ACS at 20mmHg with organ dysfunction (Milanesi & Caregnato, 2016). In the present trail, the IAP readings of both groups are within accepted level and not exceed to be IAH.…”
Section: Discussionmentioning
confidence: 46%
“…Mechanisms proposed to explain this change include reduced blood flow to the lumbar venous plexus (leading to increased pressure in the cerebrospinal fluid [CSF]), increased pressure of carbon dioxide (PaCO2), and reduced cerebral venous return by the jugular system. [12][13][14] This hypothesis meets and underlies the Monro-Kellie doctrine, in which states that the intracranial volume is equal to the volume of cerebral blood (3-10%) plus the volume of CSF (8-12%) plus the volume of brain tissue, which consists of more than 80% water. While the total intracranial volume remains identical, the ICP remains constant.…”
Section: Discussionmentioning
confidence: 74%
“…The intravesicular IAP measurement is convenient and is considered the gold standard [ 46 , 58 ]. IAP is the pressure concealed within the abdominal cavity as defined superiorly by the diaphragm, anteriorly and posteriorly by the abdominal wall, and inferiorly by the pelvic floor.…”
Section: Iap Measurement Techniquementioning
confidence: 99%